Winners and losers of globalization in Europe: attitudes and ideologies - Céline Teney; Onawa Promise Lacewell; Pieter De Wilde (European Political Science Review, 2014)
Globalization pressures result in a new ideological conflict among Europeans. We use detailed items from the Eurobarometer survey on issues of immigration and European integration that measure the ideological perspective underpinning positions toward the EU. This provides a fine-grained analysis of the ideologies underlying the poles of the new globalization-centered conflict line, which we define as cosmopolitan and communitarian. Our results show that, next to socio-demographic characteristics, subjective measurements have a considerable additional power in explaining the divide among Europeans along the communitarian–cosmopolitan dimension. Subjective deprivation, evaluation of globalization as a threat, and (sub)national and supranational identities play an important role in dividing Europeans into groups of winners and losers of globalization in both Western and Central and Eastern European countries. At the country level, the national degree of globalization is associated positively with the communitarian pole and negatively with the cosmopolitan pole in all EU countries.
Keywords: 330; globalization; societal conflict; cosmopolitanism; communitarianism; EU; immigration